Natural law ethics in theory and practice : a Joseph Boyle reader - Boyle, Joseph M., 1942- (The Catholic University of America Press, 2020)
"This volume presents a selection of previously published essays by Joseph Boyle, a crucial contributor to 20th century Catholic moral philosophy through his development of the New Classical Natural Law Theory"--